Non-Linear Instability of Pin-Ended Functionally Graded Material Arches Under Locally Distributed Radial Loads - Zhou, Jinman; Li, Guangjun; Lu, Hanwen; Chen, Zhou; Pan, Zhenyu; Zhu, Jian (Frontiers in Materials, 2022)
The arch is a common structural form in bridge engineering; its collapse is often caused by instability. In this article, in-plane nonlinear instability of pin-ended functionally graded material (FGM) arches with two cross-sectional types under local radial loads is studied. New analytical solutions to nonlinear equilibrium paths, limit point instability, bifurcation instability, and multiple limit point instability of pin-ended FGM arches under local radial load are obtained. Modified slenderness corresponding to different instability patterns of FGM arches is also derived. Comparison with the numerical results of ANSYS demonstrates that the analytical solution is accurate. The results show that cross-sectional types of FGM arches have a great influence on limit-point instability and bifurcation instability. Localized parameters increase lead-to-limit point instability load and bifurcation instability load increases, while increasing the modified slenderness ratio results in decreased limit point instability load and bifurcation instability load. In addition, a material proportion coefficient and power law index increase can also lead to limit point instability load and bifurcation instability load decrease.